Encontros e desencontros na dramaturgia do século XIX: um olhar sobre o gênero em Amélia Smith e Casa de bonecas - Selli, Maristella Letícia (2011)
This dissertation aims to provide a dialogue between the dramatic texts of Henrik Ibsen, Casa de Bonecas (1879), and Amélia Smtih (1886), by Visconde de Taunay, focusing on the convergence and discrepancies of their two main characters, Nora and Amélia. Both plays are from the XIX century, have been written during the effervescent period of the bourgeois drama, and represent the relationship that both Nora and Amélia have with their social institutions, such as the wedding, the family and the church. Another important element in this research is the constituition of the women as subjects, how their identities are shaped and how these two characters manage to transgress social constructions of the feminine. This study proposes a contemporary perspective of the female gender seen through the theoretical lenses of Lipovetsky (2000), Showalter (1994), Foucault (1979) and Lauretis (1994), seeking to evince the similarities and discprepancies of the characters in the eighteenth century from a contemporary perspective. It is also relevant to emphasise that this study is focused on the plays as literary texts and not on their teathrical productions